Absence of a role for interleukin‐13 in inflammatory bowel disease. Issue 2 (February 2014) - Biancheri, Paolo; Di Sabatino, Antonio; Ammoscato, Francesca; Facciotti, Federica; Caprioli, Flavio; Curciarello, Renata; Hoque, Syed S.; Ghanbari, Amir; Joe‐Njoku, Ijeoma; Giuffrida, Paolo; Rovedatti, Laura; Geginat, Jens; et al.
<x xml:space="preserve">Abstract</x> IL‐13 has been implicated in the pathogenesis of ulcerative colitis (UC), and may have a role in animal models of gut fibrosis. We studied the involvement of IL‐13 in inflammation and fibrosis in UC and Crohn's disease (CD). Intestinal biopsies and anti‐CD3/CD28‐ or anti‐CD2/CD28‐stimulated lamina propria mononuclear cells from UC and CD patients and control subjects were cultured, and IL‐13, IL‐4, IL‐5, IL‐17A and IFN‐γ production was measured. Mucosal IL‐13‐producing cells were characterised by flow cytometry. Gut explants from strictured CD, non‐strictured CD and healthy donors were cultured ex vivo, and secreted IL‐13, IL‐1β and collagen were measured. IL‐13 production by mucosal explants and activated lamina propria mononuclear cells did not differ between CD, UC and control subjects, and was at least a log lower than IFN‐γ and IL‐17A. IL‐13‐producing cells, and in particular natural killer T cells, were uniformly low in all groups. IL‐4 and IL‐5 were undetectable in culture supernatants. Explants of CD strictures produced low amounts of IL‐13, whereas IL‐1β and collagen were elevated. We could not confirm that UC or strictured CD are associated with elevated IL‐13 production. These data suggest that an anti‐IL‐13 Ab would not be an appropriate therapeutic strategy in inflammatory bowel disease.